PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM (Telaah Relevansi Konsep Pendidikan Dalam Kitab Ta'lim Muta'alim) - Muzammil, Muzammil (TA'LIMUNA: Jurnal Pendidikan Islam, 2012)
Ta'lim Muta'allim book is the masterpiece of imam Az-Zarnuji that has been familiar to Islamic people. Esspecially for Santri's who had attended education in Pondok Pesantren. That is the implemantation of the book one as ethical rule for those who is learning Islamic knowledge in Pondok Pesantren. Ta'lim Muta'alimm was written cause there were many student failed to get good achievement in the education process. That is not different with born process of a wiseness in our national Indonesian about Kurikulum Berbasis Kompetensi. This one cause failure to result in good achievement by unexactly educational system. The problem discussed in this journal is about this problem, what and how is the concept of education in book ta'limul muta' allim, what is used as the foundation of development prinsciples of kurikulum berbasis kompetensi and how relevant is the concept in the book Ta'limul Muta'alim with the development of prinsciples curricula in Islamic Education.